ANALYSIS OF MUUN UMKM MARKETING STRATEGY IN INCREASING BUYING INTEREST AND CUSTOMER SATISFACTION - Dwi Sagita; Nurul Alya Abdi; Muhammad Faris Al-Muzaki; Egi Utami Jailani; Rusydi Abubakar (RADJA PUBLIKA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, particularly in the culinary sector, which continues to grow rapidly. This study aims to analyze the marketing strategies implemented by MUUN Donuts in increasing purchase intention and customer satisfaction. The analysis focuses on the application of the marketing mix (4P: Product, Price, Place, Promotion), Segmenting, Targeting, and Positioning (STP) strategies, the role of customer relationship management through promotional programs, and the obstacles faced in implementing these strategies. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that MUUN Donuts has implemented its marketing strategies effectively by emphasizing product quality, competitive pricing, strategic location, and digital promotion through social media. The STP strategy targeting young consumers, students, and families is considered effective in reaching the intended market segments. Furthermore, customer relationship strategies through promotions and digital interactions have a positive impact on purchase decisions and customer loyalty. However, MUUN Donuts faces several challenges, including fluctuations in raw material prices and declining sales during academic holiday periods. Therefore, adaptive and innovative marketing strategies are needed to maintain competitiveness and ensure business sustainability.